2020
DOI: 10.1021/acsami.0c06149
|View full text |Cite
|
Sign up to set email alerts
|

Janus WSSe Monolayer: An Excellent Photocatalyst for Overall Water Splitting

Abstract: Stable photocatalysts with excellent optical adsorption and low reaction barrier are the key for the water splitting. Here, we find that a two-dimensional Janus WSSe monolayer possesses the compelling photocatalytic properties from density functional theory simulations, which can be well modulated with strain deformation. Comprehensive investigations indicate that the Janus material not only exhibits strong optical absorbance in the visible spectrum, suitable band edge potentials, high carrier separation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
213
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(257 citation statements)
references
References 53 publications
21
213
1
Order By: Relevance
“…According to Fig. 4 b, the Gibbs free energy for HER is 0.29 eV at U = 0 eV, which is much smaller than that of 2H-MoS 2 (2 eV) 34 , better than that of g-C 3 N 4 (0.54 eV) 35 and WSSe (0.58 eV) 36 , and comparable to that of recently reported Pd 4 S 3 Te 3 (0.18 eV) 37 . The Gibbs free energy change of pristine graphene for HER is also shown in Fig.…”
Section: Resultssupporting
confidence: 84%
“…According to Fig. 4 b, the Gibbs free energy for HER is 0.29 eV at U = 0 eV, which is much smaller than that of 2H-MoS 2 (2 eV) 34 , better than that of g-C 3 N 4 (0.54 eV) 35 and WSSe (0.58 eV) 36 , and comparable to that of recently reported Pd 4 S 3 Te 3 (0.18 eV) 37 . The Gibbs free energy change of pristine graphene for HER is also shown in Fig.…”
Section: Resultssupporting
confidence: 84%
“…In order to avoiding the interactions with neighboring mirror images, we set a 20 Å vacuum space vertical to each Janus WSSe bilayer, and more than 15 Å vacuum spaces along x and y directions for each Janus WSSe DWNT, whose periodic boundary condition is along the z axis. We apply the DFT-D3 approach of Grimme to address the van der Waals (vdW) force [17,23]. The Brillouin zone is regulated with a 9 × 9 × 1 gamma-pack k-mesh for the Janus WSSe bilayers, and a 1 × 1 × 7 one for the Janus WSSe double-walled nanotube.…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, compared with the Janus MoSSe monolayers, the bilayer samples have a more excellent photocatalytic performance. Lately, due to the excellent optical absorption and high carrier separation, Janus WSSe monolayer has been also reported to possess a great potential for the application of photocatalytic overall watersplitting [17]. However, for the Janus WSSe bilayer, the photocatalytic properties is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite latest advances, there is still plenty of room to improve the catalytic activity and selectivity of CO 2 reduction in order to satisfy large-scale industrial applications. Recent studies have shown that electric polarization plays an important role in determining catalytic activities and selectivities, and can greatly improve the catalytic performance compared with the unpolarized counterparts 19 21 . For instance, Janus TM dichalcogenides possess better catalytic abilities for water splitting and N 2 fixation 19 21 , since the catalysis-related properties, including surface stoichiometry, electronic structure 22 – 26 , adsorption strengths, and reaction activation energies, can be tuned by the polarization 27 ; Moreover, by utilizing the polarization from the substrate, the overpotential of oxygen evolution reaction on TiO 2 surface can be strongly reduced 28 .…”
Section: Introductionmentioning
confidence: 99%